Comparative analysis of the performance of the Flax engine and Unity - Szelug, Wojciech (Journal of Computer Sciences Institute, 2022)
This article compares the two game engines Unity and Flax engine. The research consisted in comparing the efficiency of individual engines using two similar applications. The first one generates from several hundred to several thousand physical objects and examines the efficiency of engines in terms of physics simulations. The second application generates a forest area filled with the same tree model. The application aims to study the behavior of the engine for various graphics settings. In both applications, parameters such as the number of frames per second, consumption of the processor, graphics card and RAM were tested. Research shows that Unity is more efficient than Flax Engine.